USING A 3D MODELLING TO CALCULATE THE VOLUMES OF OVERBURDEN ROCKS AND MINERALS - Alvanyan, A. K.; Ovsyannikov, M. V. (Vestnik Permskogo universiteta. Serii͡a︡ Geologii͡a, 2022)
The volumes of overburden rocks and minerals were calculated based on the 3D model of the deposit, which was created using results of analysis of the geological structure of the deposit, and construction of the topographic surface. A comparative table of the results of calculating the volumes of overburden rocks and minerals was compiled using the method of geological blocks and 3D models